Interaction between FTO rs9939609 and the Native American-origin ABCA1 rs9282541 affects BMI in the admixed Mexican population - Marisela Villalobos-Comparán; Bárbara Antuna-Puente; María Teresa Villarreal-Molina; Samuel Canizales-Quinteros; Rafael Velázquez-Cruz; Paola León-Mimila; Hugo Villamil-Ramírez; Juan Antonio González-Barrios; José Luis Merino-García; María Rocío Thompson-Bonilla; Diego Jarquin; Osvaldo Erik Sánchez-Hernández; et al. (BMC, 2017)
Abstract Background The aim of this study was to explore whether interactions between FTO rs9939609 and ABCA1 rs9282541 affect BMI and waist circumference (WC), and could explain previously reported population differences in FTO-obesity and FTO-BMI associations in the Mexican and European populations. Methods A total of 3938 adults and 636 school-aged children from Central Mexico were genotyped for both polymorphisms. Subcutaneous and visceral adipose tissue biopsies from 22 class III obesity patients were analyzed for FTO and ABCA1 mRNA expression. Generalized linear models were used to test for associations and gene-gene interactions affecting BMI, WC and FTO expression. Results FTO and ABCA1 risk alleles were not individually associated with higher BMI or WC. However, in the absence of the ABCA1 risk allele, the FTO risk variant was significantly associated with higher BMI (P = 0.043) and marginally associated with higher WC (P = 0.067), as reported in Europeans. The gene-gene interaction affecting BMI and WC was statistically significant only in adults. FTO mRNA expression in subcutaneous abdominal adipose tissue according to ABCA1 genotype was consistent with these findings. Conclusions This is the first report showing evidence of FTO and ABCA1 gene variant interactions affecting BMI, which may explain previously reported population differences. Further studies are needed to confirm this interaction.